Long COVID and Its Impacts: A Case–Control Study in Brazil - Cristina M. Ruas; Maria Laura Silva; Ana L. G. F. Figueiredo; Amanda P. de Alencar; Samuel de S. Melo; Geovani F. de Castro; Natália V. Carobin; Melina A. Cordeiro; Janete F. R. Aguirre; Amanda F. M. de Oliveira; Adriano de P. Sabino (Biomedicines)
Introduction: Long COVID, or post-COVID-19 syndrome, refers to a set of persistent symptoms following SARS-CoV-2 infection without another identifiable cause. Studies indicate that symptoms can last for up to two years and affect multiple body systems. Objective: The objective of this study is to compare symptom prevalence between infected individuals pre and post-COVID-19 and non-infected individuals in a population from Southeastern Brazil. Materials and Methods: A case–control study was conducted with participants from the MonitoraCovid program in a university in Brazil. The study included adults who responded to a questionnaire about long COVID symptoms. Data were collected virtually between October 2023 and May 2024. Results: Of the 2886 individuals eligible for analysis, 75.5% reported having been positive for COVID-19. Most participants were vaccinated, with 82.99% receiving two doses. In the pre and post comparison, individuals who had COVID-19 were more likely to report increased symptoms after infection, with 95.5% of assessed conditions worsening, particularly cognitive and respiratory issues. A comparison between those who had and had not been infected with COVID-19 showed that only 6.67% of symptoms were more prevalent in the infected group. The most significant post-COVID-19 symptoms included memory problems, fatigue, and shortness of breath, though some conditions, such as anxiety and sleep disturbances, were less common among those who had COVID-19. Conclusions: The findings reinforce that long COVID significantly impacts cognitive health, highlighting the importance of monitoring previously infected individuals. The study also emphasizes the need for further research in Global South contexts to better understand the long-term implications of COVID-19.